2005
DOI: 10.1186/1476-069x-4-25
|View full text |Cite
|
Sign up to set email alerts
|

Increasing work-place healthiness with the probiotic Lactobacillus reuteri: A randomised, double-blind placebo-controlled study

Abstract: BackgroundShort term illnesses, usually caused by respiratory or gastrointestinal diseases are disruptive to productivity and there is relatively little focus on preventative measures. This study examined the effect of the probiotic Lactobacillus reuteri protectis (ATCC55730) on its ability to improve work-place healthiness by reducing short term sick-leave caused by respiratory or gastrointestinal infections.Methods262 employees at TetraPak in Sweden (day-workers and three-shift-workers) that were healthy at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
90
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 10 publications
1
90
2
3
Order By: Relevance
“…Based on our present results, the Bifidobacterium strain might not be the most optimal strain against respiratory infections. Indeed, it is mainly probiotic strains from Lactobacillus genera-L. rhamnosus GG [34] , L. casei DN-114001 [35] , a combination of L. gasseri PA 16/8, B. longum SP 07/3 and B. bifidum MF 20/5 [5][6] , and L. reuteri [36] -that have reduced the incidence or symptoms of common cold or respiratory tract infections. However, the immunomodulatory effects underlying the results observed in these studies have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our present results, the Bifidobacterium strain might not be the most optimal strain against respiratory infections. Indeed, it is mainly probiotic strains from Lactobacillus genera-L. rhamnosus GG [34] , L. casei DN-114001 [35] , a combination of L. gasseri PA 16/8, B. longum SP 07/3 and B. bifidum MF 20/5 [5][6] , and L. reuteri [36] -that have reduced the incidence or symptoms of common cold or respiratory tract infections. However, the immunomodulatory effects underlying the results observed in these studies have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…LGG + LC705 + PJS + Bb99 DH5α GAS THS LGG LC705 1129 161 1/10 Bb12 Bb99 ARH74 PIA2 PJS THS LGG LC705 1129 161 1/10 Bb12 Bb99 ARH74 PIA2 [36][37][38][39][40] . It is of interest that for example L. rhamnosus GG has been effective in immune mediated diseases even though in the present study we observed that LGG induced very low cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…reuteri ATCC 55730 is a commercial probiotic strain that survives in the human intestine (34) and has beneficial effects in clinical trials of infant diarrhea, colic, and IgE-dependent eczema (29,30,33,36). L. reuteri was also shown to be effective in protecting interleukin-10 (IL-10)-deficient mice against spontaneous colitis (22).…”
mentioning
confidence: 99%